2018
DOI: 10.1007/s00277-018-3254-4
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy and chemotherapy induced haemophagocytic lymphohistiocytosis in children and adolescents—a single centre experience of 20 years

Abstract: Haemophagocytic lymphohistiocytosis (HLH) is a possibly life-threatening syndrome of immune dysregulation and can be divided into primary (hereditary) and secondary forms (including malignancy-associated HLH (M-HLH)). We retrospectively analysed epidemiological, clinical, virological and laboratory data from patients with M-HLH treated at our department between 1995 and 2014. Out of 1.706 haemato-/oncologic patients treated at our department between 1995 and 2014, we identified 22 (1.29%) patients with seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 19 publications
(27 reference statements)
3
47
0
Order By: Relevance
“…In our cases, the median age of children with M-HLH was 7 years old, which is consistent with other reports [9][10][11]. Due to the increased incidence of malignancy with age, the age of onset of M-HLH children is older than other types of HLH, especially primary HLH.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our cases, the median age of children with M-HLH was 7 years old, which is consistent with other reports [9][10][11]. Due to the increased incidence of malignancy with age, the age of onset of M-HLH children is older than other types of HLH, especially primary HLH.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies showed that children with acute leukemia (AL) are more likely to suffer from M-HLH than those with lymphoma [10,11,13,14], other studies indicated lymphoma was more common than AL in M-HLH children [9]. Furthermore, HLH occurred significantly more often in the children with AML, T cell lymphoma and T/NK-cell lymphoma than those with B-ALL or B cell lymphoma [9][10][11]13], which corresponded with our study. Based on the relationship of HLH and malignancy or chemotherapy, M-HLH can be classified into malignancy-triggered HLH (HLH at onset of malignancy) and HLH occurring during chemotherapy (Ch-HLH).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, M-HLH should not preclude a complete genetic evaluation. 16 The largest multicenter study in children with M-HLH was performed in Turkey and reported its association with acute lymphoblastic leukemia (66.6% of cases), AML (7.4% of cases), Hodgkin lymphoma (HL), non-HL, rhabdomyosarcoma, neuroblastoma, and Langerhans cell histiocytosis. This study showed that HLH occurred predominantly during leukemia treatment.…”
Section: Discussionmentioning
confidence: 99%